(untitled) (Fiep Bulletin - online, 2016)
The mechanical ventilation weaning (MVW) is defined as a moment of transition that goes from the mechanical support to the spontaneous ventilation in patients that remain under MV for a period longer than 24 hours. A strategy that can accelerate the weaning process is the use of physiotherapy, which through weaning techniques and protocols has been showing to succeed in the process. The objective of this study was to realize, based on Brazilian scientific literature, a critical analysis on the intervention and effects of physiotherapy when applied to patients during the MV weaning process. By means of a systematic review, complete and free articles published in Portuguese between January of 2000 and May of 2014, related to the theme were considered for the study. The research included LILACS and SciELO data bases, using as descriptor the words, “physiotherapy”, “weaning” and “mechanical ventilation”. 2175 articles were initially found, however only 16 qualified for the study. These articles showed techniques of physiotherapy and their effects on the mechanical ventilation weaning process. There are several techniques applied in patients during the process that result in a favorable and beneficial outcome for the patient, and that also imply in a shorter term for the use of mechanical ventilation, weaning, decreased rates of recurrence of intubation, shorter term hospitalization and finally, decreased mortality rates.